ANCAMAN CAPITAL INFLOW - Teguh Sihono; Rohaila Yusof (Informasi, 2011)
Capital inflow can be interpreted as an increase in the amount of money available from external or foreign sources for the purchase of local capital assets such as securities, houses, buildings, land, machinery. These short-term asset purchase, so if at any time be withdrawn in large quantities, it will endanger the country's economy. The swift flow of foreign funds may be a threat to the country which became the capital inflow in the form of options: pressure of inflation, high cost economy, the defisit Central Bank balance, the economic turbulence, and the threat of economic growth. Improvement of high economic growth accompanied by rising foreign exchange reserves that high also, it turns out is not free from the risk of unbridled inflation and economic cricis, destabilizing the economy during those funds withdrawn by foreign investors. For the avoidance of economic risk, should the government together with the Central Bank made a rule to direct capital inflow into the real sektor. Keywords: capital inflows, global likuiditas